Finite Element Analysis of Concrete Beam under Flexural Stresses Using Meso-Scale Model - Alaa H. Al-Zuhairi; Ali Ihsan Taj (Salehan Institute of Higher Education, 2018)
Two dimensional meso-scale concrete modeling was used in finite element analysis of plain concrete beam subjected to bending. The plane stress 4-noded quadrilateral elements were utilized to model coarse aggregate, cement mortar. The effect of aggregate fraction distribution, and pores percent of the total area – resulting from air voids entrapped in concrete during placement on the behavior of plain concrete beam in flexural was detected. Aggregate size fractions were randomly distributed across the profile area of the beam. Extended Finite Element Method (XFEM) was employed to treat the discontinuities problems result from double phases of concrete and cracking that faced during the finite element analysis of concrete beam. Cracking was initiated at a small notch located at the middle of the bottom face of the concrete beam. The response of plain concrete beam subjected to pure bending via two point load application was detected using (XFEM) analysis of meso-scale concrete model. Assuming full bond between aggregate particles, and mortar at interfacial zone, the flexural strength of plain concrete beam is increased when aggregate particles size is increased, so that bending and shear stress were affected by void percentage and aggregate particles distribution. The maximum deflection at midspan was increased when the aggregate particles size decreases.